Potensi Kabupaten Belitung Sebagai Kawasan Pengembangan Sapi Potong - Erbowo, B.; Cyrilla, L.; Priyanto, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
Belitung District is one region in Indonesia where economy of the society relies on the mining sector, especially tin. Tin mining gave a substantial contribution to national development. And that is why in fact the role of the livestock sector is relatively small compared to the mining sector. The purpose of this study is to evaluate the resources that were available in Belitung District for beef cattle development to reduce the dependence on meat outside the region. This study was designed as a survey. The sample was 30 farmers that were taken purposively. Data was analysed descriptively based on the increase capacity of ruminant population (KPPTR) and SWOT analysis. The result showed that Belitung District can add capacity of ruminant’s population for about 39.672,909 Animal Unit (AU). Farmers did not have enough skill in husbandry management. Technologies that have been developed to improve the productivity of livestock are artificial insemination (IB) and biogas system. Based on the components of beef cattle development area, Belitung District was identified as assisted region. Development programme of the beef cattle region in the future should consider the quality of human resources and socio-economic conditions of farmers in achieving goals. The role of government was needed to improve farmer’s skill and ability in farming, husbandry technology adoption and mastery of the development process so that beef cattle industry can be more focused. Based on SWOT analysis some improvement should do in Belitung district to make this region as a developed cattle region, that are: increase land for forages cultivation; improve farmer’s skill especially in disease management to reduce livestock mortality; increase quantity of extension agent who has animal husbandry specialization; improve some facilities needed for beef cattle development for example holding ground, farm equipment’s distributor, and Artificial Insemination service point; empowering groups of farmers to motivate the farmers in achieving goals.